PENGARUH UKURAN KAP, KOMPLEKSITAS DAN RISIKO PERUSAHAAN TERHADAP AUDIT FEE - Ajeng Irmawati (2023)
This research is quantitative study that aims to determine the effect of auditor size, corporate risk and company complexity on audit fees. The objects of this research are non-financial companies listed on Indonesia Stock Exchange (IDX) in 2020-2022. The samples of this research is 357 using purposive sampling. Hypothesis testing in this research used multiple linear regression analysis using STATA software with a significance level 5%. The result of the data analysis, it can be concluded that (1) Auditor size has a positive effect on audit fees, (2) Company Complexity has no effect on audit fees, (3) Firm risk has no effect on audit fees and control variable (4) Company Size has a positive effect on audit fees.